The control factor our struggle to see the true threat - Siegel, Bill (Hamilton Books, 2012)
The control factor explores the psychological maneuvers, fantasies, and entanglements we engage in to avoid clearly seeing the Islamic threat that confronts us. The prerequisite for developing necessary strategies to ensure our survival is taking responsibility for our perceptions and actions and holding our enemy responsible for theirs